Scars of oxidative stress: protein carbonylation and beta cell dysfunction in diabetes - Ling, Ashley; Schultz, Katherine R.; Knight, Jefferson D.; Shearn, Colin T.; Baumel-Alterzon, Sharon (Frontiers in Endocrinology, 2025)
Type 1 and type 2 diabetes are characterized by a profound loss of functional β-cell mass, driven by mechanisms that are still not fully understood. A spectrum of β-cell stressors drives this loss, including oxidative stress (OS). Unlike most cells, β-cells express unusually low levels of key antioxidant enzymes, rendering them highly susceptible to OS. Protein carbonylation (PC), a major hallmark of OS, is an irreversible modification that can be generated by covalent addition of lipid peroxidation products known as “reactive lipid aldehydes” (RLAs) into proteins, resulting in protein inactivation, misfolding, aggregation, degradation and formation of neo-antigens. PC plays a critical role in the pathogenesis of various human diseases, including diabetes. Increased RLAs and PC are found in islets, plasma, red blood cells and adipose tissue in diabetic patients and in diabetic rodent models. Limited studies, including ours, have globally mapped carbonylated proteins in pancreatic islets and specifically in β-cells. Yet no one has explored which proteins undergo carbonylation in human islets in diabetes and whether their carbonylation contributes to the loss of functional β-cell mass in T1D and T2D. Cells have three cellular lines of defense against accumulation of PC: antioxidant enzymes, phase I and II metabolic enzymes that detoxify RLAs, and degradation of carbonylated proteins by 20S proteasome and lysosome. Since genes encoding all three lines of defense are controlled by the antioxidant master regulator, NRF2, activating this factor might be more advantageous than using pharmacological carbonyl scavengers. Future studies should test whether NRF2 activation can effectively reduce PC and preserve functional β-cells in diabetes.